WISATA OUTBOND PANTAI TANJUNG BURUNG KOTA MEMPAWAH - Faharsyahga Fitzki Alwannanda; Hamdil Khaliesh; Emilya Kalsum (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
The city of Mempawah, also known as the earth of galaherang, has lots of tourist destinations. This is because the it has regional characteristics in the form of land and coastal islands with seas. There is a potential beach tourism destination in there which has mangrove ecosystem in it, namely Tanjung Burung Beach. However, the current condition of it is still not optimal due to a lack of supporting facilities as an ecotourism area, which causes activities in it to become monotonous and less attractive. In an effort to maximize the potential of areas that have characteristics in the form of sandy and muddy soils, outbound tourism areas can be designed with attractive activities and can be carried out in all types of environmental conditions. The design of the Mempawah City Tanjung Bird Beach aims to create a playground for visitors that is formed based on the potential and problems of each by adjusting the playings that can be applied to take advantage of the surrounding natural conditions. The design of this outbound tourism area focuses on the Tanjung Burung Beach area using the glass box design method which is carried out sequentially to produce an attractive outbound tourism design concept by applying ecotourism principles to outbound play spaces to minimize damage and preserve the surrounding environment to make it a sustainable tourist area.